Agricultura do cuidado e a criação de novas práticas sociais : uma contraposição à forma de vida capitalista neoliberal - Santo, Thais Marques de (2021)
The Green Revolution was the process that created the conditions for the penetration and diffusion of neoliberal ideology in agriculture. The technical and technological innovations and the transformations it fosters create a new way of relating to agricultural products, a new paradigm of feeding and commercialization. These changes affect in different ways the lives of producers and consumers, who, in turn, are faced with practical problems derived from this mode of production and commercialization, and as a consequence, need to collectively develop social practices to solve these problems. Considering that the form of life forged by neoliberal capitalism is not able to guarantee the conditions for the development of the social learning necessary to solve the problems it engenders, it is necessary to seek in social practices that are foreign to neoliberalism, such as those produced by alternative forms of agriculture, the way to solve these problems. As a reference of alternative models, we analyze agroecological and organic family farming and propose the notion of care agriculture as their synthesis, since we argue that the ethical-normative principle that underlies these alternative forms of agriculture is care. This principle is taken as constitutive of being and linked to the way human beings realize their existence in the world, but especially as a product of sociability. We want to argue that the form of life that is being created by care agriculture has its ethical basis in caring for oneself, for others, and for nature; and its normative foundation is emancipatory relationships based on social freedom, autonomy, and solidarity. The general objective of this tesisis to verify whether or to what extent the social practices produced by care agriculture are capable of pointing to an alternative form of life to the neoliberal capitalist form of life. Our study is qualitative and is divided into two parts: a critique of the neoliberal capitalist form of life and an empirical investigation about the formation of an alternative project, a form of life antagonistic to the established one. The empirical stage is composed of primary and secondary data.